Analiza formalna filmu – analiza warsztatowa – analiza „partyturowa”…(?) - Czyżewski, Stefan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The text Analiza formalna filmu – analiza warsztatowa – analiza ‘partyturowa [Formal analysis of film – workshop analysis – score notation analysis] is recalling the rules of “score notation analysis”, popularized by professor Bolesław Włodzimierz Lewicki in the 1960s, when he was the dean and lecturer at the Łódź history. Interestingly, the method was not well received by the students and critics. The historical perspective also appears in the curriculum of the time and has been utilized by Lewicki as a “reference system”. Thusly, it is the entirety of his concept and the theoretical background available at the time. Feridun Erol’s example score notation analysis of the movie The Last Day of Summer is an integral part of the text. Another reason – more important, since it is still valid – is the noticeable deficiency of workshop analyses and the function of means of expression in shaping a film. This state of affairs is probably the result of peculiar and de facto difficult knowledge on filmmaking, and even if theoreticians are familiar with this field, there are legitimate worries a reader unacquainted with it may be lost.